2023
DOI: 10.1002/cl2.1340
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: In‐person interventions to reduce social isolation and loneliness: An evidence and gap map

Abstract: This is the protocol for an evidence and gap map. The objectives are as follows: This EGM aims to map available evidence on the effects of in‐person interventions to reduce social isolation and/or loneliness across all age groups in all settings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Policymakers should also ensure that the work they quote includes study populations that are well-represented in all relevant demographics and that the research is able to make causal claims about how loneliness impacts health. The World Health Organisation (WHO) and the European Union have identified the limits of their own knowledge and skills in this field, commissioning experts to write evidence gap reports [ 66 , 67 ] or GB and DK for example have had loneliness researchers help write their vision and strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policymakers should also ensure that the work they quote includes study populations that are well-represented in all relevant demographics and that the research is able to make causal claims about how loneliness impacts health. The World Health Organisation (WHO) and the European Union have identified the limits of their own knowledge and skills in this field, commissioning experts to write evidence gap reports [ 66 , 67 ] or GB and DK for example have had loneliness researchers help write their vision and strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The EU has taken the lead as the first supranational union to address loneliness amongst its member states by recently organizing various roundtables and conferences around loneliness [ 70 ]. Globally, WHO has recently published an evidence gap report on in-person interventions for reducing social isolation and loneliness [ 67 ]. Lastly, we argue that policies would be meaningless if there are no concrete funding streams allocated towards evidence generation, intervention design and implementation and the evaluation thereof.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the Campbell Collaboration guidance for producing an evidence and gap map (White et al, 2020) described in our protocol (Welch et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…13 For inperson interventions on loneliness and social isolation across all age groups, 421 studies and 92 systematic reviews were identified. 14 We now need an overall synthesis of the findings from intervention studies to be undertaken with an implementation lens to derive clear recommendations of which interventions work, for whom, and in what contexts.…”
Section: C) Identifying Effective Interventions For Implementation At...mentioning
confidence: 99%
“…15 Access to these tools could inform evidence-based policy and programs and help direct funding towards research priorities. 13,14 Priority 2 -Adopting a whole-ofsystems approach…”
Section: Priority 1 -Strengthening the Evidencementioning
confidence: 99%